Humor as a Part of Interpersonal Communication - Karpenko, Hanna (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the description and analysis of humor, irony, sarcasm in our life. Different points of view on humor are presented. Theories of the origin of humor (relief, incongruity, superiority) are described. It’s proved that humor is a part of interpersonal communication and it is irreplaceable characteristic and the quality people always seek in other ones. Some features of humor and the categories of irony (verbal, situational and dramatic) are demonstrated. The advantages of using humor by teachers in the classroom are stated. Some episodes from the lives of students in which they use humor, irony and sarcasm are presented. It’s stressed that people were born with the gift of laughter that lifts their spirits, makes them feel happy. The article states that a sense of humor is a good characteristic that helps people to live happily, to stay younger, to endure problems and to influence other people positively